Developing a different voice: The life and work of Carol Gilligan. Issue 1 (5th December 2022) - Josselson, Ruthellen
Abstract: Objective: To explore the psychobiographical origins of Carol Gilligan's sensitivity to the importance of voice in human psychology, an awareness that, through her foundational written work, transformed the field. Method: Narrative inquiry and analysis. Results: Carol Gilligan's awareness of voice began at a young age with a self‐defining memory in which she learned to hold on to her own voice and experience. She never set out to be a social change agent, but she became one. Other scholars relied on her work, particularly the lyrical trope of "in a different voice" to change social (and psychological) attitudes toward women in many ways. This psychobiographical analysis traces Carol's personal struggles to sustain her own voice and knowledge, and these struggles met a culture that became able to hear something about how the patriarchal culture suppresses relational sensibilities. Rooted in a close and intense relationship with her mother, who expressed and imposed on her a duality between the voice of personal experience and the voice of meeting social expectations. Carol's understanding of the differing levels of what it means "to know" grounded a new conception of girls' development as well as of moral development. Conclusion: Carol Gilligan became an agent of social change because her inner world and life path coincided with sociocultural readiness to embrace her work as giving voice to an emerging awareness of the suppression and denigration of women's sensibilities in psychology as well as in the larger culture. Her lifelong conflicts about speaking her own truth versus conforming to a society in which she was well able to be successful attuned her to the ways in which others, particularly women, similarly discounted their own experience.